Motherhood as the Vehicle for Change in Australian Adolescent Women of Preterm and Full-Term Infants. (November 2016) - Sheeran, Nicola; Jones, Liz; Rowe, Jennifer
Preterm birth represents an interruption to the normal development of maternal identity and is considered a highly stressful event for adult mothers. However, no research has investigated whether or how preterm birth affects the adolescent mother's transition to motherhood. The current study aimed to explicate the experience of being a mother for adolescent women who experienced a preterm or term birth in Australia. This Interpretative Phenomenological Analysis Study analyzed interviews with 14 primiparous, English-speaking adolescent mothers (15-19 years; 10 preterm and 4 full term) who participated in three interviews over a 12-month period. Findings suggested few differences in the experience of being a mother due to infant birth status. Instead, the experience of being a mother was fundamentally about transformations to the self. The young women constructed themselves differently as a result of being mothers. Changes included moving away from delinquent behaviors, development of internal resources, growth of a positive view of self, gaining meaning in their lives, and reconciling idealized and actual notions of self and other. This research adds to our understanding of how motherhood shapes the adolescent women's lives, while also challenging our assumptions about the impact of preterm and full-term birth for adolescent mothers.